Question :
![\sf{ \frac{x - 3}{9} - \frac{x - 2}{10} = 1 - \frac{x}{12}} \sf{ \frac{x - 3}{9} - \frac{x - 2}{10} = 1 - \frac{x}{12}}](https://tex.z-dn.net/?f=%5Csf%7B+%5Cfrac%7Bx++-+3%7D%7B9%7D++-++%5Cfrac%7Bx+-+2%7D%7B10%7D+%3D+1+-++%5Cfrac%7Bx%7D%7B12%7D%7D++)
Answers
Answered by
10
Multiplying both sides of the equation by 180, the LCM of 9,10 and 12, we get
(x - 3) × 20 - (x - 2) × 18 = (12 - x/12) × 180
20x - 60 - 18x + 36 = (12 - x) × 15
20x - 18x - 60 + 36 = 180 - 15x
2x - 24 = 180 - 15x
2x + 15x = 180 + 24
17x = 204
Hence, x = 12
Answered by
21
Answer:
This is your answer.
Hope it will help you..
Attachments:
![](https://hi-static.z-dn.net/files/d50/a5c56812c1f1808c8cb5f29e0bdc274a.jpg)
![](https://hi-static.z-dn.net/files/d5f/c5f54fe4fcb9ef09448d36aa6756cb72.jpg)
Similar questions